Language use and choice in selected Malaysian agricultural organisations - Bhar, Sareen Kaur (2016)
How organisations cope and manage language matters in the workplace is largely absent from research literature. This is because language and communication has been a surprisingly neglected subject of research in the agricultural workplace domain as it is an area often overlooked by organisations in Malaysia and throughout the world. Addressing this gap,language practices of three selected agricultural organisations from Malaysia are investigated. More specifically, this study investigates to what extent English and other languages are used within the communicative practices in the workplace of these organisations and the underlying factors that govern language choice. Furthermore, the study explores the dominant role of English and other languages in the communicative practices of the selected agricultural based companies. Three complementary theoretical frameworks are used to examine language use and choice in the agricultural workplace domain which are, Fishman’s (1972) concept of who speaks what language to whom,Transactional Process Model (Adler and Towne, 1999), and Giles and Coupland’s (1991) communication accommodation theory are used to examine and explore the complex and dynamic language practices of the managers and employees in these organisations. Data were collected using the quantitative approach by using questionnaire. To support the quantitative findings, a qualitative approach based on interviews, observation and document and website analysis were also used. The results show that there is a flexibility where both employers and employees typically will use a language that works best for a given situation and always in the best interest of the organisation. The employers and employees highly value the role of English as the lingua franca in the agricultural business domain as it plays a critical and dynamic part related to career mobility and progression. Lastly, implications for the study indicate that language practices in the agricultural industry are contrary to the Malaysian language policy.